2018
DOI: 10.5530/ijper.52.4s.81
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged in vivo Stinging Nettle Treatment Impacts on Functional Capacity of Leukocytes in Immunologically Mature Chickens

Abstract: Objective:The experiment aimed at establishing the effects of an alcoholic Urtica dioica extract on the in vitro blastogenic response in antigen stimulated, immunologically mature chickens. Materials and Methods: Three equal groups (n=17) of 47 days old, Rock x Cornish chickens were subjected to oral administration of: a) 0.5 ml/chicken/ day of an alcoholic stinging nettle extract (I), b) 0.5 ml/chicken/day alcohol (II, solvent control), and c) 0.5 ml chicken/day water (III-environment control) for seven days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In this experimental work, we have assessed the ameliorative role of UD extract on oocyte maturation against deleterious effects of RA (in a high dosage, which causes side effects in oocyte cells). Positive effects of UD extract have been reported in several studies for controlling pro-inflammatory cytokine, immunologic response to stress, glucose transporters, and lipid peroxidation in different organs [ [27] , [28] , [29] ]. For example, Yıldızhan et al [ 30 ] investigated the UD protective effects on liver tissue injury and antioxidant capacity in irradiated rats, and revealed that UD extract reduces the radiation oxidative stress and degenerative changes of liver.…”
Section: Discussionmentioning
confidence: 99%
“…In this experimental work, we have assessed the ameliorative role of UD extract on oocyte maturation against deleterious effects of RA (in a high dosage, which causes side effects in oocyte cells). Positive effects of UD extract have been reported in several studies for controlling pro-inflammatory cytokine, immunologic response to stress, glucose transporters, and lipid peroxidation in different organs [ [27] , [28] , [29] ]. For example, Yıldızhan et al [ 30 ] investigated the UD protective effects on liver tissue injury and antioxidant capacity in irradiated rats, and revealed that UD extract reduces the radiation oxidative stress and degenerative changes of liver.…”
Section: Discussionmentioning
confidence: 99%